2012
DOI: 10.1111/j.1748-7692.2012.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of estimating marine mammal diets: A review of validation experiments and sources of bias and uncertainty

Abstract: Diet estimation in marine mammals relies on indirect methods including recovery of prey hard parts from stomachs and feces, quantitative fatty acid signature analysis (QFASA), stable isotope mixing models, and identification of prey DNA in stomach contents and feces. Experimental evidence (9 species/13 studies) shows that digestion strongly influences the proportion and size of otoliths that can be recovered in feces. Number correction factors (NCF) and digestion coefficients have been experimentally determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 83 publications
2
151
0
Order By: Relevance
“…Although initially we hypothesized that the digestion of prey DNA would be less than that of algal pigments because of the greater stability of DNA compared to photosynthetic pigments (chlorophyll a), these studies indicated that, at least in copepods, prey DNA digestion was significant. Similar results have been reported in other studies with copepods (Durbin et al, 2012), other marine crustaceans (Tobe et al, 2010) and a wide variety of other marine and terrestrial predators (Bowen and Iverson, 2013;Hunter et al, 2012;Weber and Lundgren, 2009). However, it is difficult to predict based on first principles whether prey digestion will be a significant impediment to the quantification for specific predators.…”
Section: Prey Digestionsupporting
confidence: 80%
“…Although initially we hypothesized that the digestion of prey DNA would be less than that of algal pigments because of the greater stability of DNA compared to photosynthetic pigments (chlorophyll a), these studies indicated that, at least in copepods, prey DNA digestion was significant. Similar results have been reported in other studies with copepods (Durbin et al, 2012), other marine crustaceans (Tobe et al, 2010) and a wide variety of other marine and terrestrial predators (Bowen and Iverson, 2013;Hunter et al, 2012;Weber and Lundgren, 2009). However, it is difficult to predict based on first principles whether prey digestion will be a significant impediment to the quantification for specific predators.…”
Section: Prey Digestionsupporting
confidence: 80%
“…Diet studies using stomach contents have well known biases (Tollit et al, 2010;Bowen and Iverson, 2012). Stomach contents represent some portion of an individual's most recent feeding activity.…”
Section: Data Limitationsmentioning
confidence: 99%
“…quantitative versus qualitative and species versus general trophic level) and they also differ in time scale (i.e. more recent diet versus longer-term diet) (reviewed in Bowen & Iverson 2013). To our knowledge, only a few studies have combined the 3 methods to assess the foraging ecology of marine mammals (Hooker et al 2001, Jansen 2013.…”
Section: Introductionmentioning
confidence: 99%